Local Tourism Marketing Strategy Through the Revitalization of Tourist Products and Word of Mouth - AHMAD, Alifian Rizzalul; NURJANNAH, Diana Kusuma (Journal of Tourism Economics and Policy, 2025)
This study aims to analyze the effect of tourism product revitalization and word of mouth on tourists' visit decisions through the mediating role of destination image. The research was conducted in Rembangan Tourism Area, Jember, using a quantitative explanatory approach. Data were collected from 100 respondents who had visited the destination at least once, through purposive sampling technique. Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method was employed for data analysis using SmartPLS 3.0 software. The results show that tourism product revitalization has a significant and positive effect on both destination image and visit decisions. Destination image also has a strong and positive impact on visit decisions. However, word of mouth does not show a significant influence on either destination image or visit decisions. Additionally, the moderating effect of destination image in the relationship between both independent variables and visit decision was not supported. These findings suggest that revitalizing tourism products is a more influential strategy for encouraging tourist visits, while destination image plays a critical role in enhancing the attractiveness of the tourism destination.